2014
DOI: 10.1038/nbt.3011
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific antimicrobials using efficiently delivered RNA-guided nucleases

Abstract: Current antibiotics tend to be broad spectrum, leading to indiscriminate killing of commensal bacteria and accelerated evolution of drug resistance. Here, we use CRISPR-Cas technology to create antimicrobials whose spectrum of activity is chosen by design. RNA-guided nucleases (RGNs) targeting specific DNA sequences are delivered efficiently to microbial populations using bacteriophage or bacteria carrying plasmids transmissible by conjugation. The DNA targets of RGNs can be undesirable genes or polymorphisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
662
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(691 citation statements)
references
References 39 publications
18
662
1
10
Order By: Relevance
“…The effectiveness of the CRISPR-Cas system in eliminating plasmid DNA and lytic phages is well established (1,2,15,19,26). Nevertheless, its utility in clinical settings as a tool to render pathogens sensitive to antibiotics and to reduce horizontal gene transfer of resistance determinants has only recently been demonstrated (16,17). We believe that the strategy provided here can be applied to different pathogen-phage systems as phages can be found for most of the pathogens, and a compatible CRISPR-Cas system should work in many pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the CRISPR-Cas system in eliminating plasmid DNA and lytic phages is well established (1,2,15,19,26). Nevertheless, its utility in clinical settings as a tool to render pathogens sensitive to antibiotics and to reduce horizontal gene transfer of resistance determinants has only recently been demonstrated (16,17). We believe that the strategy provided here can be applied to different pathogen-phage systems as phages can be found for most of the pathogens, and a compatible CRISPR-Cas system should work in many pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent elegant studies demonstrated that phage-transferable CRISPR-Cas systems are capable of specifically killing pathogens or resensitizing them to antibiotics (16,17). These studies, and another study (13), also showed that the transferred CRISPR-Cas system is capable of eliminating specific bacterial populations.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Two independent teams believe they could have a farreaching solution in the gene editing technology CRISPR, which allows them to tailor therapies to specific resistance mutations. 1,2 The most promising application of the findings is the potential to resensitize resistant bacteria to standard antibiotics, but the researchers will have Figure 1. CRISPR's double-edged knife.…”
Section: By Stephen Parmley Senior Writermentioning
confidence: 99%
“…Cas9 can change the sensitivity and responses of cells to discovered drug, evidenced by the finding that CRISPR/Cas RGNs could alter the resistance of multidrugs in the model of a Galleria mellonella infection (Citorik et al 2014). The preliminary findings from Church and his colleagues showed that Cas9 could inactivate 62 porcine endogenous retroviruses (PERVs) in pig embryos (Nature News 2016).…”
mentioning
confidence: 99%